(untitled) (Research, Society and Development, 2020)
São Bento do Una - PE is the largest egg producer in the Northeast and the fourth in Brazil, according to information from the Avicultural Association of Pernambuco. At the base of the poultry feed we have corn and soybeans, grains that have been showing high prices, directly impacting production costs. Aiming at his self-sufficiency in the production of corn, the poultry farmer could try to produce this component, for that it is essential to know the regional climate, for making the planting decision and the appropriate management to be applied to the crop. As a result, the objective was to determine the suitability and climatic zoning for corn, identifying its productive potential in São Bento do Una (PE), as a support for poultry farming. The rainfall and thermal data correspond to the years 1920 to 2019, were obtained from the Pernambuco Water and Climate Agency. The aptitude classification criteria proposed by the Brazilian Agricultural Research Company were used to classify the studied area. São Bento do Una has moderate aptitude for planting corn. São Bento do Una records moderate aptitude for planting corn. As the Iv was 36 and there is DEF in most of the year, irrigated planting should be encouraged, as well as the use of early cultivars, in order to take advantage of the rainy season, making crop irrigation mandatory, being a strategy to reduce production risk for maize.